2009
DOI: 10.3767/000651909x474122
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy, ecology, and conservation status of Philippine Rafflesia (Rafflesiaceae)

Abstract: The number of Rafflesia species (Rafflesiaceae) reported for the Philippines has grown explosively from two before 2002 to ten or eleven presently. We present an overview of the current knowledge of Philippine Rafflesia by providing a comprehensive account of all the recognized species with their taxonomy, distribution and ecology, plus a key and photographs to aid in identification. Their conservation status and that of the rain forest habitats they require is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
57
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 19 publications
2
57
1
Order By: Relevance
“…Several factors, including an earlier shift in the developmental timing of diaphragm initiation, the effective reduction in the perianth lobes, and the architectural remodeling of the chamber itself, could have contributed to the stabilization of these enormous flowers. Support for this hypothesis comes from the occurrence of lobed (imperfectly formed) diaphragms in Rafflesia, which are restricted to species of small size [e.g., Rafflesia lobata Barcelona & Pelser (32)]. Further investigation within Rafflesia will help to better address this question, but overall, our study highlights the surprising and dynamic nature of morphological evolution among the "greatest prodigy of the vegetable kingdom" (6).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Several factors, including an earlier shift in the developmental timing of diaphragm initiation, the effective reduction in the perianth lobes, and the architectural remodeling of the chamber itself, could have contributed to the stabilization of these enormous flowers. Support for this hypothesis comes from the occurrence of lobed (imperfectly formed) diaphragms in Rafflesia, which are restricted to species of small size [e.g., Rafflesia lobata Barcelona & Pelser (32)]. Further investigation within Rafflesia will help to better address this question, but overall, our study highlights the surprising and dynamic nature of morphological evolution among the "greatest prodigy of the vegetable kingdom" (6).…”
Section: Discussionmentioning
confidence: 88%
“…In terms of our identification of the Rafflesia diaphragm as the petal whorl, it is interesting to note that considerable variation in diaphragm morphology is observed in many species of Rafflesia. Some have distinctly lobed diaphragms, and others have reduced diaphragms that form a small shelf at the chamber opening (32). Elucidating the developmental basis of this variation may shed light on the modification of this floral organ.…”
Section: Discussionmentioning
confidence: 99%
“…that was between 51-60 cm beared higher number of buds compared to other smaller and younger size of Tetrastigma. The occurrence and especially the well-being of the host plant are very crucial for Rafflesia to grow [31]. This showed that Tetrastigma that already matured was suitable for the buds to grow effectively.…”
Section: Results and Findingsmentioning
confidence: 99%
“…(Vitaceae ;Meijer 1997;Nais 2001;Pelser et al 2016). The Philippines is one of the centers of Rafflesia diversity (Barcelona et al 2009) and is home to 13 currently recognized species (Pelser et al 2011 onwards;Barcelona et al 2014;Galindon et al 2016), which are all endemic to the country. Rafflesia lagascae Blanco (1845) is arguably the most common Rafflesia species in the Philippines and has the largest distributional area (Barcelona et al 2009).…”
mentioning
confidence: 99%
“…This is potentially a significant conservation factor, because the Philippine tropical rainforest, to which this species is confined, has been reduced to an estimated 3-6% of its original cover (Mittermeier et al 1998;Ong et al 2002). Moreover, remaining tropical forest habitat has become highly degraded and fragmented as a result of human activities such as logging, mining, and land conversion for agriculture (Barcelona et al 2009). To better understand the conservation needs of R. lagascae and to improve its management, information about its patterns of genetic diversity and genetic structure are needed.…”
mentioning
confidence: 99%